Management of Acute Coronary Syndrome Indonesia : Insight from One ACS Multicenter Registry - Juzar, Dafsah Arifa; Muzakkir, Akhtar Fajar; Ilhami, Yose Ramda; Taufiq, Nahar; Astiawati, Tri; R A, I Made Junior; Pramudyo, Miftah; Priyana, Andria; Hakim, Afdhalun; Anjarwani, Setyasih; Endang, Jusup; Widyantoro, Bambang (Jurnal Kardiologi Indonesia, 2022)
Background Acute coronary syndrome (ACS) is a life-threatening disorder which contributes to high morbidity and mortality in the world. Registry of ACS offers a great guidance for improvement and research. We collated a multicentre registry to gain information about demographic, management, and outcomes of ACS in Indonesia. Methods IndONEsia Acute Coronary Syndrome Registry (One ACS Registry) was a prospective nationwide multicenter registry with 14 hospitals participating in submitting data of ACS via standardized electronic case report form (eCRF). Between July 2018 and June 2019, 7634 patients with ACS were registered. This registry recorded baseline characteristics; onset, awareness, and transfer time; physical examination and additional test; diagnosis; in-hospital medications and intervention; complications; and in-hospital outcomes. Results Nearly half of patients (48.8%) were diagnosed with STE-ACS. Most prevalent risk factors were male gender, smoking, hypertension. Patients with NSTE-ACS tended to have more concomitant diseases including diabetes mellitus, dyslipidemia, prior AMI, HF, PCI, and CABG. Majority of ACS patients in our registry (89.4%) were funded by national health coverage. Antiplatelet, anticoagulant, antihypertensive, and statins were prescribed as 24-hours therapy and discharge therapy; however presription of potent P2Y12 inhibitor was low. More STE-ACS patients underwent reperfusion therapy than non-reperfusion (65.2% vs. 34.8%), and primary PCI was the most common method (45.7%). Only 21.8% STE-ACS patients underwent reperfusion strategy within 0-3 hours of onset. Invasive strategy performed in 17.6% of NSTE-ACS patients, and only 6.7% performed early (within <24 hours). Patients underwent early invasive strategy had a shorter median LoS than late invasive strategy (P<0.001). A shorter median LoS also found in intermediate and low risk patients. Mortality rate in our ACS patients was 8.9%; STE-ACS patients showed higher mortality than NSTE-ACS (11.7 vs. 6.2%). Conclusion Our registry showed a comparable proportion between STE- and NSTE-ACS patients, with male gender predominant in middle age. Both STE- and NSTE-ACS sharing the same risk factors. We need an improvement in referral time, especially in patients with STE-ACS. Evidence from our registry showed that there are two issues that need to be addressed in order to improve ACS outcomes: optimal and adequate medical treatment and invasive strategy. This article has a related Erratum.